Hubungan Pengetahuan dengan Efikasi Diri Pada Caregiver Keluarga Pasien Gangguan Jiwa Di RSJD Dr. RM. Soedjarwadi - Pratama, Bayu Despriyanto; , Arif Widodo, A.Kep., M.Kes (2017)
Background: Another term mental disorder is psychosis. One example of psychosis is schizophrenia. Schizophrenia is a maladaptive condition in psychological and physiological that makes a person's behavior disturbed. 1.7 per mil in Indonesian indicates the prevalence of severe mental disorder and Central Java Province is in the top five mental disorders. The role of the family is important in the task of maintaining health. Caregiver family of patients mental disorders into one determining factor achieved maximum mental health. Therefore, caregiver is important to have good knowledge and self efficacy in an effort to maximize health maintenance one mental health. Purpose: This study aims to determine the relationship of knowledge with self efficacy in caregiver family of patients with mental disorders in RSJD Dr. RM. Soedjarwadi. Object and Method: The object of research is caregiver family of mental patiens who visit in the outpatient with total sample 95 respondents. The research design is using descriptive correlative with cross sectional study approach. Data analysis to know correlation in research using spearman rank test (rho). Result: The value of spearman rank test (rho) sows zhitung 0.704 and p value 0.001. The family caregiver knowledge of mental patients in RSJD Dr. RM. Soedjarwadi is self sufficient, the family caregiver self efficacy of mental patients in RSJD Dr. RM. Soedjarwadi is moderate. Conclucion: There is a significant correlation relationship of knowledge with self efficacy on caregiver family of mental patients in RSJD Dr. RM. Soedjarwadi.